Disease characteristics of diffuse large B‐cell lymphoma predicting relapse and survival after autologous stem cell transplantation: A single institution experience. Issue 1 (3rd December 2019) - Gaut, Daria; Romero, Tahmineh; Oveisi, David; Howell, Grant; Schiller, Gary
Abstract: While various tools such as the International Prognostic Index (IPI) and its derivatives exist for risk‐stratification of diffuse large B‐cell lymphoma (DLBCL) at diagnosis, patient and disease characteristics capable of predicting outcome after high‐dose chemotherapy followed by autologous stem cell transplantation (HDC/ASCT) are not clearly defined. We retrospectively analyzed medical records of 111 DLBCL patients (78 relapsed and 33 refractory) who underwent HDC/ASCT at our institution from 2010‐2015. After a median follow‐up time of 4.6 years (interquartile range [IQR] 2.2‐8.1), the likelihood of 5‐year progression‐free survival (PFS) was 62.2% (95% CI, 53.4%‐72.4%) and the likelihood of 5‐year overall survival (OS) was 68.9% (95% CI, 60.7%‐78.2%). More than three chemotherapy regimens prior to ASCT was the only variable associated with lower likelihood of PFS ( P = .004) and OS (P = 0.026). Male gender and high IPI score at time of ASCT were also associated with lower likelihood of PFS ( P = .043; P = .013). NCCN IPI and age‐adjusted IPI at time of ASCT were not predictive of outcome following ASCT. Patients with refractory and relapsed disease had similar outcomes post‐ASCT ( P = .207 for PFS, P = .073 for OS).